SIMULATORS OF GEOLOGICAL AND GEOMORPHOLOGICAL PROCESSES: CONTRIBUTIONS TO EDUCATION AND TRAINING IN GEOSCIENCES AND EARTH SCIENCES - Oliveira Pimenta, Joao Paulo de [UNESP]; Moroz Caccia Gouveia, Isabel Cristina [UNESP]; Messias Correia, Ronaldo Celso [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2019)
The teaching of Geography, especially in the area of Geomorphology, presupposes a capacity, on the part of the teacher, to make understandable several phenomena and processes that, often, are beyond the empirical knowledge of the student. Thus, using didactic resources such as models, models and multimedia equipment becomes necessary to facilitate the representation of different dynamics that, at different scales, become difficult to understand. In view of this, we present two simulators of geological and geomorphological dynamics constructed from the initiative of students and professors of the Geology, Geomorphology and Water Resources Laboratory of FCT / UNESP, with the aim of contributing to the teaching of Geomorphology and Geosciences in general, mainly regarding the teaching of phenomena related to tectonisms, surface runoff and erosive processes.
Keywords: Geomorphology; Geography Teaching; Relay Simulator